The effects of regular training on spinal posture: a fitness and bodybuilding perspective - Bingöl, Mustafa; Ünver, Şaban; Mor, Hakkı; Berk, Yunus; Ceylan, Tülay; Günay Derebaşı, Deniz; Aydın, Yağmur Naz; Akman, Tülin; Küçük, Hamza; Ceylan, Levent (Frontiers in Physiology, 2025)
BackgroundRegular training is associated with better postural alignment, decreased risk of musculoskeletal problems, and improved overall physical function. The aim of this study was to examine the changes in the spinal postures of individuals who regularly engage in fitness and bodybuilding training.MethodsA total of 252 male individuals between the ages of 20–28 (mean age: 23.71 ± 1.81 years), who either engage in fitness and bodybuilding training (athletes) (n = 125; age 23.61 ± 1.78 years; sports age 5 ± 0.89 years) and those who do not engage in sports (sedentary) (n = 127; age 23.82 ± 1.83 years) participated in the study. A spinal Mouse device was used in the measurements. In spine measurement, all spinal protrusions from C7 to S1 were evaluated. T-test and correlation tests were used to analyze the data.ResultsA statistically significant difference was detected between the athlete and sedentary groups regarding the degrees of thoracic kyphosis, lumbar lordosis, and sacral kyphosis (p < 0.05). However, no difference was observed in the upright posture (p > 0.05).ConclusionIt was found that there were significant differences in some spinal curves of fitness and bodybuilding trainees compared to sedentary, but the values were within physiological limits and did not indicate negative effects. The study may provide new insights into the effects of fitness and bodybuilding training on spine health, and individuals can incorporate training with proper form and technique into their lifestyle for spinal health.